2019
DOI: 10.1080/10400435.2019.1644685
|View full text |Cite
|
Sign up to set email alerts
|

The use of everyday information communication technologies in the lives of older adults living with and without dementia in Sweden

Abstract: Background: Increasingly services and interventions involve everyday information communication technologies (EICTs) in provision, however, use of EICTs among people with dementia is little known. Therefore, this study aimed to investigate the relevance, use, and ability to use EICTs between a group of older adults with dementia and a comparison group with no known cognitive impairment. Method: Interviews with 35 people with dementia, 34 comparison participants using the standardized Everyday Technology Use Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…For example, one such study in Sweden using the ETUQ, which interviewed people between 2015 and 2017, included those who did not consider themselves ICT users. This study reported computers perceived as relevant among 62% of their older adults without cognitive impairment, and 49% of adults with dementia [20]. Contra to this, the report from an earlier 2015 pilot survey in Sweden, acknowledged bias in favour of ICT users, which the authors encouraged readers to accommodate.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…For example, one such study in Sweden using the ETUQ, which interviewed people between 2015 and 2017, included those who did not consider themselves ICT users. This study reported computers perceived as relevant among 62% of their older adults without cognitive impairment, and 49% of adults with dementia [20]. Contra to this, the report from an earlier 2015 pilot survey in Sweden, acknowledged bias in favour of ICT users, which the authors encouraged readers to accommodate.…”
Section: Introductionmentioning
confidence: 74%
“…This means that those who consider themselves 'non-users' or who find ICT difficult to use are underrepresented, as they are more likely to decline to participate [19]. It has repeatedly been found that groups of people with dementia consider lower amounts of ET, including ICT, relevant to them in comparison to older adults with no known cognitive impairment [3,20]. Furthermore, it has been shown that the amount of ETs used by older adults with cognitive impairment decreases as the impairment progresses [21].…”
Section: Introductionmentioning
confidence: 99%
“…those living in rural areas), and many of the considerations highlighted in this article will be pertinent to them. It has been shown that PwD living alone can experience difficulties using the telephone and other everyday technology such as mobile telephones and electronic devices [ 22 24 ], therefore remote consultation methods may not be as accessible to these patients who require support and/or adaptations. Healthcare professionals should be cognisant of this when suggesting to use these technologies.…”
Section: Medicines Management Issues For People With Dementia During mentioning
confidence: 99%
“…To date, the amount of Everyday Technologies (ETs) reported relevant and the perceived ability to use them has been shown to overlap, but be significantly lower among groups with dementia, mild cognitive impairment, and subjective cognitive impairment, in comparison to groups with no known cognitive impairment (Malinowsky et al, 2017;Nygård et al, 2012). Additionally, ability to use ET correlated strongly with the amount of information and communication ETs (ICTs) reported relevant only among a group with mild stage dementia and not at all among the control group (Wallcook et al, 2019). Subsequently, a lesser amount of ETs used out of home (i.e., smartphones, computers, card payment machines, ticket machines, lift access, keypads) were shown to be relevant to a group of people with dementia in comparison to controls, and this coincided with going to significantly fewer places outside home (Gaber et al, 2019).…”
Section: Occupational Science;mentioning
confidence: 99%